2021
DOI: 10.1155/2021/9936157
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Severity of Depression, Anxiety, and Stress among Medical Undergraduate Students of Arsi University and Their Association with Substance Use, Southeast Ethiopia

Abstract: Background. Mental problems can negatively impact physical and psychological well-being of junior medical students and predispose them to many unhealthy behaviors. Objective. We aimed to determine the prevalence and severity of depression, anxiety, and stress among medical undergraduate students of Arsi University and their association with substance use. Methods. Institutional-based cross-sectional study was conducted on 265 sampled medical students. Participants were selected by systematic random sampling. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 34 publications
(32 reference statements)
1
14
2
2
Order By: Relevance
“…In contrast, research conducted in Ethiopia reported a lower incidence of the disorders among university students (Simegn et al, 2021;Melaku et al, 2021). The high prevalence rate of depression, anxiety, and stress reported in this study can be explained by the ongoing war conflict in the university area, which can increase the burden of mental distress among students, as other research suggests (Madoro et al, 2021;Elhadi et al, 2020).…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…In contrast, research conducted in Ethiopia reported a lower incidence of the disorders among university students (Simegn et al, 2021;Melaku et al, 2021). The high prevalence rate of depression, anxiety, and stress reported in this study can be explained by the ongoing war conflict in the university area, which can increase the burden of mental distress among students, as other research suggests (Madoro et al, 2021;Elhadi et al, 2020).…”
Section: Discussioncontrasting
confidence: 67%
“…This might be due to the instance that male students receive a lower-level of social support (McLean et al, 2022;Alsubaie et al, 2019;Hefner & Eisenberg, 2009). However, consistence with previous research female students reported a higher level of stress compared to their counterparts (McLean et al, 2022;Simegn et al, 2021;Melaku et al, 2021;Habihirwe et al, 2018).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Atualmente, vem-se observando um aumento no número de ocorrências de pessoas com estresse e depressão cuja manifestação pode influenciar a qualidade de vida e as atividades de rotina (1)(2)(3) . O sintoma de estresse é compreendido como uma manifestação resultante de um evento do meio externo ou interno que excede os aspectos de adaptação fisiológica ou psicológica referente ao processo cognitivo, emocional e comportamental, deixando as pessoas em situações de risco para o adoecimento (4) .…”
Section: Introductionunclassified